2006
DOI: 10.1189/jlb.0306196
|View full text |Cite
|
Sign up to set email alerts
|

Factors masking HMGB1 in human serum and plasma

Abstract: High mobility group box 1 protein (HMGB1) is a ubiquitously expressed architectural chromosomal protein. Recently, it has become obvious that HMGB1 can also act as a proinflammatory mediator when actively secreted during cell activation or passively released from necrotic cells. HMGB1 appears to play an important role in the pathogenesis of diseases, including sepsis and rheumatoid arthritis. However, easy, sensitive, and reliable detection systems are required to investigate the clinical significance of HMGB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 24 publications
12
137
1
4
Order By: Relevance
“…We observed a modest correlation between HMGB1 levels obtained by ELISA and those from Western blots, in accord with results described by Urbonaviciute, et al 7 . Considering the potential human serum factors including HMGB1-specific antibodies masking HMGB1 7 , it is plausible that the total circulating HMGB1 levels detected by Western blotting are higher than those detectable by ELISA.…”
Section: To the Editorsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed a modest correlation between HMGB1 levels obtained by ELISA and those from Western blots, in accord with results described by Urbonaviciute, et al 7 . Considering the potential human serum factors including HMGB1-specific antibodies masking HMGB1 7 , it is plausible that the total circulating HMGB1 levels detected by Western blotting are higher than those detectable by ELISA.…”
Section: To the Editorsupporting
confidence: 81%
“…Amounts of HMGB1 were also determined in parallel with Western blots in 20 patients 7 . For statistical analysis nonparametric tests were employed due to unequal data distribution.…”
Section: To the Editormentioning
confidence: 99%
“…We analyzed our samples with a commonly used Western blot method, whereas Wibisono used a commercial ELISA. However, Urbonaviciute et al (36) found a discrepancy between Western blot and ELISA results, suggesting that serum/plasma components bind to HMGB1 and interfere with its detection by ELISA systems (36).…”
Section: Discussionmentioning
confidence: 99%
“…Wahrscheinlich sind daf ü r maskierende Faktoren wie HMGB1-Antik ö rper, Lipoplysaccharide oder IL-1-β verantwortlich, die an HMGB1 binden und so die Erkennung des Molek ü ls im ELISA verhindern [144] . Eine Vorbehandlung mit Perchlors ä ure f ü hrt zur Abl ö sung dieser Faktoren [137] .…”
Section: Nachweism ö Glichkeiten Im Blutunclassified
“…Au ß erdem k ö nnen beim Western Blot auch Background-Proteine dargestellt werden, was R ü ckschl ü sse auf die Spezifit ä t des Testes zul ä sst [137,144,145] .…”
Section: Nachweism ö Glichkeiten Im Blutunclassified